Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose Circulating tumor DNA (ctDNA) could be a powerful prognostic biomarker for patients with locally advanced esophageal cancer but higher sensitivity is needed. An ultrasensitive test could enable improved treatment decision-making by accurately identifying patients with residual disease. Experimental design 331 plasma samples from 36 patients were collected both preoperatively and postoperatively. We applied MAESTRO-Pool (Minor Allele Enriched Sequencing Through Recognition Oligonucleotides) of the Broad Institute and the Oncodetect® V2 test of Exact Sciences, two MAESTRO-based, ultrasensitive, tumor-informed, mutation enrichment sequencing tests, to all samples. Results With the Oncodetect V2 test, we found 9 of 14 patients (64%) with recurrence and postoperative plasma available tested ctDNA-positive at their first postoperative sample and all 14 patients tested ctDNA-positive for at least one postoperative sample prior to recurrence. ctDNA was detected below the limit of detection for first-generation assays in 59% of all samples in which we detected ctDNA. By tracking a median of 2.1-fold more mutations per patient (up to 5,000 total mutations per patient), the Oncodetect V2 test showed highly concordant results (98.9% positive percent agreement), improved ctDNA detection, and longer lead times to recurrence as compared to MAESTRO-Pool. Conclusion ctDNA detection after curative-intent therapy for locally advanced esophageal cancer had strong positive and negative predictive values for recurrence. Given the low ctDNA levels observed, and that all patients with recurrence were eventually ctDNA-positive, ctDNA testing in esophageal cancer may benefit from ultrasensitive tests that detect part-per-million levels of ctDNA.